2000
DOI: 10.1007/pl00008142
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore-induced ethylene suppresses a direct defense but not a putative indirect defense against an adapted herbivore

Abstract: Herbivory induces both direct and indirect defenses in plants; however, some combinations of these defenses may not be compatible. The jasmonate signal cascade activated both direct (nicotine accumulations) and indirect (mono- and sesquiterpene emissions) whole-plant defense responses in the native tobacco Nicotiana attenuata Torr. Ex Wats. Nicotine accumulations were proportional to the amount of leaf wounding and the resulting increases in jasmonic acid (JA) concentrations. However, when larvae of the nicoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
225
2
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(245 citation statements)
references
References 39 publications
13
225
2
4
Order By: Relevance
“…Using detached lima bean leaves (Phaseoluslunatus L), [71] demonstrated that exogenous applications of the ethylene precursor, 1-aminocyclopropane-1-carboxylic acid, enhance JA-induced VTC emission. However, in tobacco (Nicotiana attenuata), [72] did not detect any significant interactions between exogenous methyl jasmonate and ethylene upon in- Current study contradicts reports of VTC-dependent ethylene senescence or vice versa. In a study to determine the effect of ethylene on VTC synthesis and how their interaction affect postharvest balsam fir needle abscission through the inhibition of ethylene synthesis using aminoethoxyvinylglycine (AVG), it was discovered that although AVG was effective in inhibiting ethylene synthesis and delaying postharvest needle abscission there was no changes in the type and amount of VTCs synthesized compared to the control [15].…”
Section: Stress Senescence and The Role Of Vtcscontrasting
confidence: 56%
“…Using detached lima bean leaves (Phaseoluslunatus L), [71] demonstrated that exogenous applications of the ethylene precursor, 1-aminocyclopropane-1-carboxylic acid, enhance JA-induced VTC emission. However, in tobacco (Nicotiana attenuata), [72] did not detect any significant interactions between exogenous methyl jasmonate and ethylene upon in- Current study contradicts reports of VTC-dependent ethylene senescence or vice versa. In a study to determine the effect of ethylene on VTC synthesis and how their interaction affect postharvest balsam fir needle abscission through the inhibition of ethylene synthesis using aminoethoxyvinylglycine (AVG), it was discovered that although AVG was effective in inhibiting ethylene synthesis and delaying postharvest needle abscission there was no changes in the type and amount of VTCs synthesized compared to the control [15].…”
Section: Stress Senescence and The Role Of Vtcscontrasting
confidence: 56%
“…9) Fatty acid-amino acid conjugates in the oral secretions of two Manduca species elicited bursts in the production of jasmonic acid 5) and ethylene. 5,10) These results clearly show that volicitin-related compounds evoked some plant defense responses.…”
mentioning
confidence: 65%
“…The induced increase in JA levels that are normally proportional to the amount of mechanical wounding erupts into a JA burst that increases concentrations two to 10 times wound-induced levels (McCloud and Kahl et al, 2000;Ziegler et al, 2001) and is propagated throughout the damaged leaf ahead of the rapidly foraging herbivore (Schittko et al, 1999). Wounding and JA-elicitation do not result in ethylene emissions, but tobacco hornworm attack produces a rapid ethylene burst, which is sustained during larval feeding .…”
Section: Why Does N Attenuata Alter Its Wound-and Ja-elicited Responmentioning
confidence: 99%